PENGEMBANGAN INSTRUMEN PENILAIAN DIRI BERBASIS PEMBELAJARAN KONTEKSTUAL - Sari Yustiana; Nuhyal Ulia (Universitas Muhammadiyah Surakarta, 2019)
This research is aimed to (1) develop contextual-learning-based self-assessment components and instruments, (2) investigate the quality of the developed instruments. This development research applied the procedures developed by Borg Gall. The validity of the instruments employed the content validity with Aiken’ V formula, while the reliability of the instruments employed Cronbach Alpha. The development of the instruments produces learning topics and assessment instruments along with the rubrics. The expert judgment shows that the products are categorized ‘Good’. The content validity is categorized ‘Valid’. The reliability of the instruments is categorized ‘Reliable’ with Cronbach Alpha 0.7 and the instruments are practical.